Conditional privacy-protection remote user authentication mechanism for WBAN - Jin CAO; Yi-qing ZHENG; Hui LI (Tongxin xuebao)
A conditional privacy-protection remote user authentication scheme based on a certificateless group signature was proposed,which can accomplish the anonymous mutual authentication between the user and the remote doctors.In addition,when the doctors perceived that users were in case of an emergency,the mechanism enabled the only group manager (GM) to expose the real identity information of users and given users timely assistance.The scheme can provide the anonymity,traceability,mutual authentication,non-reputation and some other security features.The performance analysis results show the scheme is more suitable for WBAN.